Proximal radius fracture morphology following axial force impact: a biomechanical evaluation of fracture patterns - Lacheta, Lucca (BMC Musculoskelet Disord, 2019)
BACKGROUND: The most common location for articular fractures of the radial head is often reported to be the anterior lateral aspect of the radial head with the arm in neutral position. However, these findings mainly base on clinical observations rather than precise biomechanical measurements. The purpose of this study was to evaluate the formation of proximal radius fractures, the association between axial forces and fracture morphology, energy to failure and bone stiffness in a biomechanical in-vitro setup. METHODS: 18 fresh-frozen cadaveric radii performed axial load compression with 10 mm/min loading until bone failure. Energy to failure and bone stiffness were recorded. Proximal radial head fracture morphology and affection of the anterolateral quadrant were optically analyzed. RESULTS: All radii survived a compression load of 500 N. The mean compressive forces that lead to failure were 2,56 kN (range 1,30 – 7,32). The mean stiffness was 3,5 kN/mm (range 2,0 – 4,9). 11 radial neck fractures and 7 radial neck and radial head multifragment fractures were documented. The anterolateral quadrant was involved in 78% of tested radii. CONCLUSION: The anterolateral quadrant of the radial head (in neutral position of the forearm) is confirmed to be the most common location for articular radial head fractures in a biomechanical setting. In case of a fall on the outstretched arm radial neck fractures should be securely ruled out due to prior occurrence to radial neck and head fractures.